Foliar fertilization in Bermuda grass DiscoveryTM - Jefferson Oliveira Silvério; Patrick Luan Ferreira dos Santos; Matheus Vinícios Leal do Nascimento; Camila Aparecida Nunes de Souza; João Victor Costa; Roberto Lyra Villas Bôas (Ornamental Horticulture, 2020)
Bermuda grass DiscoveryTM is a new variety of ornamental and sports turfgrass with a unique color (bluish green), which has great potential to grow in Brazil. However, information regarding its development is still incipient, mainly related to the management of foliar fertilization. Thus, the aimed was to evaluate the development of Bermuda grass DiscoveryTM based on doses of foliar fertilizer. The experiment was carried out in the experimental area, in 2019 autumn; and the experimental design was completely randomized, with 4 treatments and 3 repetitions, totaling 12 experimental plots of 1.5 m2 each. The treatments were: 0 mL L-1 (Control), 50 mL L-1, 75 mL L-1 and 100 mL L-1 of the foliar fertilizer: NPK (6-2-3 + 20% amino acids). The applications were carried out with costal spray, in the late afternoon (17h), to avoid losses by evapotranspiration, and the evaluations were daily over 15 days. The following were evaluated: chemical analysis of the soil, green color index, height of the lawn, dry mass of the clippings and analysis by digital image. It was observed that with the doses increasing, there was better development and coloring of the lawn, showing that foliar fertilization is an effective and quick response method for the turfgrass, with the need for regular applications in an interval of 7 days to maintain the quality desired aesthetics. However, this variety presents low vertical growth, consequently less need for maintenance of cut compared to the other Bermuda grass. The dose of 75 mL L-1 is recommended for the management of the species.